People, plants, place, and rules: the Nagoya Protocol in pacific island countries. (27th January 2016) - Robinson, Daniel F.; Forsyth, Miranda
Abstract: This paper considers the rules informing the use of plants and associated knowledges in the Pacific, particularly Vanuatu, in the context of the introduction into the Pacific region of the Nagoya Protocol on Access to Genetic Resources and the Fair and Equitable Sharing of Benefits Arising from their Utilization to the Convention on Biological Diversity. The Nagoya Protocol, which entered into force in October 2014, brings both new international regulatory dimensions and new recognition and re‐framing of local and customary levels of regulation over genetic resources and traditional knowledge. Whilst generally seen as a positive step to protect genetic resources and traditional knowledge from misappropriation, at an implementation level the Nagoya Protocol gives rise to a range of issues. These issues go to the heart of questions about power, agency, and resource allocation, the bounded nature of communities and their relationship with land or sea; the fluidity and dynamism of customary law; challenges stemming from multiples sites of agency and the potentials of pluralism in many respects. We explore these issues with specific reference to some examples in Vanuatu, the Cook Islands and Samoa.